Identifikasi Kesulitan Guru PAI Kota Medan dalam Implementasi Kurikulum 2013 - Muhammad Alpin Hascan; Tasman Hamami (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
The implementation of the 2013 Curriculum until now is increasingly reaping problems. Although this curriculum has been running for seven years, it seems that this curriculum still has obstacles in some schools, especially in the field of Islamic religious education studies. This research aims to find out and examine the difficulties experienced by PAI teachers in implementing the 2013 Curriculum in the city of Medan. This research uses a descriptive qualitative approach that is studied through literature studies. Data collection was obtained through interview techniques with PAI teachers in Medan. The results of this study show that there are several difficulties experienced by PAI teachers in the implementation of the 2013 Curriculum, including lack of understanding of the teacher itself with the content of the 2013 curriculum as a whole, inadequate facilities as a means of support in supporting learning. Some learning materials require a time allocation that is more than the specified time. The solution offered in this case first; increased knowledge and application of the 2013 curriculum for teachers. It can be done by following open discussions, training and other intellectual activities. In addition, teachers are required to be creative in designing learning through innovative media and good learning strategies and methods.